ACCIDENT INSURANCE FOR INFORMAL SECTOR WORKERS IN INDONESIA - Sri Denti On Madya; Atik Nurwahyuni (Media Kesehatan Politeknik Kesehatan Makassar, 2019)
Workplace accidents are unwanted and unexpected events that can cause loss of life and property. The Social Security Law in Indonesia mandates that Work Accident Guarantees be mandatory for every workforce in Indonesia. To see how work accident insurance for informal sector workers in Indonesia. This research was carried out by library study method. The subjects of this study are data in the form of articles and several source books related to the theme of the research, namely concerning workplace accidents and social security of informal sector workers in Indonesia. The number of work accidents, especially in the informal sector in Indonesia, still tends to be high, especially in construction work. Policies in the field of occupational health and safety (K3) still focus on formal sector workers rather than informal worker. Keyword: work accident, social security, informal sector